1977
DOI: 10.1139/v77-038
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of certain α-diazocarbonyl compounds with thiophosgene and ethyl chlorodithioformate

Abstract: The reaction of thiophosgene with α-diazocarbonyl compounds produced mixtures of 1,2,3-and 1,3,4-thiadiazoles, in which the latter predominated, irrespective of whether the bis(α-diazoacyl)mercury derivatives or the free diazo compounds were used. In contrast, ethyl chlorodithioformate gave exclusively 1,3,4-thiadiazoles with α-diazocarbonyl compounds in the presence of triethylamine and only 1,2,3-thiadiazoles when the bis(α-diazoacyl)mercury derivatives were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Bacchetti and coworkers 407 showed that reaction of 4-chlorobenzoyldiazomethane (240b) with thiophosgene yields 2-chloro-5-( 4-chlorobenzoyl)·l ,3,4-thiadiazole (244a) along with two more products, t.~>-chloro-4-chloroacetophenone (245a) and 246, while treatment of ~nitrobenzoyldiazomethane (240c) with thiophosgene afforded 2-chloro-5-( 4-nitrobenzoyl)-1 ,3,4-thiadiazole (244b) and t.~>-Chloro-4-nitroacetophenone (245b) (Scheme 70). 47 The above controversy was solved by Demaree et al 408 who reported that the reaction of thiophosgene with a-diazocarbonyl compounds (240) produces mixtures of 4-(4-substituted benzoyl)-5-chloro-1,2,3-thiadiazoles (241) and 2-chloro-5-(4-substituted benzoyl)-1-3,4-thiadiazoles (244) with the latter predominating irrespec- tive of whether the free diazo compound or its bis(a-diazoacyl) mercury derivatives were used. The mechanism of the formation of 241 and 244 has also been discussed (Scheme 71).…”
Section: Reaction With Diazo Compounds and Azidesmentioning
confidence: 99%
“…Bacchetti and coworkers 407 showed that reaction of 4-chlorobenzoyldiazomethane (240b) with thiophosgene yields 2-chloro-5-( 4-chlorobenzoyl)·l ,3,4-thiadiazole (244a) along with two more products, t.~>-chloro-4-chloroacetophenone (245a) and 246, while treatment of ~nitrobenzoyldiazomethane (240c) with thiophosgene afforded 2-chloro-5-( 4-nitrobenzoyl)-1 ,3,4-thiadiazole (244b) and t.~>-Chloro-4-nitroacetophenone (245b) (Scheme 70). 47 The above controversy was solved by Demaree et al 408 who reported that the reaction of thiophosgene with a-diazocarbonyl compounds (240) produces mixtures of 4-(4-substituted benzoyl)-5-chloro-1,2,3-thiadiazoles (241) and 2-chloro-5-(4-substituted benzoyl)-1-3,4-thiadiazoles (244) with the latter predominating irrespec- tive of whether the free diazo compound or its bis(a-diazoacyl) mercury derivatives were used. The mechanism of the formation of 241 and 244 has also been discussed (Scheme 71).…”
Section: Reaction With Diazo Compounds and Azidesmentioning
confidence: 99%
“…:3, as determined by NMR. only 2-(4-chlorobenzoyl)-5-(ethylthio)-l,3,4-thiadiazole (type F), whereas with bis(4chloro-a-diazophenacy1)mercury in MeCN the isomeric 4-(4-~hlorobenzoyl)-5-(ethylthio)-l,2,3-thiadiazole (type E) was formed exclusively [41]. In a similar reaction, 2-(methoxycarbony1)ethyl chlorodithioformate and CH,N, in Et,O at 0" gave a 1 :2 mixture of the corresponding 1,2,3-and 1,3,4-thiadiazoles [42], and CH,N, and methyl dithioacetate at -70" yielded 5-methyl-l,2,3-and 2-methyl-I ,3,4-thiadiazole together with 2-methyl-2-(methylthio)thiirane (20,45, and 22 % yield, resp.)…”
mentioning
confidence: 99%